Organometallic compounds as carriers of extraterrestrial cyanide in primitive meteorites - Karen E. Smith (Nature Portfolio, 2019)
Cyanide is thought to be crucial for the origin of life. Here, the authors showed that iron cyanocarbonyl complexes are present in meteorites and propose that these compounds were a source of free cyanide on early Earth and served as precursors to the active sites of ancient hydrogenases.